Observer-Based Robust Control for Switched Stochastic Systems with Time-Varying Delay - Guoxin Chen; Zhengrong Xiang; Hamid Reza Karimi (Abstract and Applied Analysis)
This paper investigates the problem of observer-based robust control for a class of switched stochastic systems with time-varying delay. Based on the average dwell time method, an exponential stability criterion for switched stochastic delay systems is proposed. Then, performance analysis and observer-based robust controller design for the underlying systems are developed. Finally, a numerical example is presented to illustrate the effectiveness of the proposed approach.